EFEK DEKOKTA DAUN PULUTAN (Urena lobata) TERHADAP KADAR Superoxide Dismutase (SOD) JARINGAN OTAK DAN MOTILITAS IKAN ZEBRA (Danio rerio) FASE JUVENIL YANG DIPAPAR MALATHION SECARA KRONIS - Alvian Nur Firdaus; Ariani Ratri Dewi; Yudi Purnomo (Jurnal Kedokteran Komunitas, 2020)
Introduction: Malathion is a pesticide that could inhibit cholinesterase’s action on acetylcholine and also producing free radicals that can affect the nervous system. Decocta of Urena lobata leaves has antioxidant and neuroprotective potential. This study aims to prove the effect of Urena lobata leaf decocta on superoxide dismutase (SOD) levels and swimming speed of juvenile Danio rerio exposed to chronic malathion.Method: This is an in vivo experimental laboratory study with a post-test only control group design using Danio rerio on 40 days old divided into 2 control groups and 3 treatment groups (n = 5). The fishes exposed to malathion for 40 days in all groups except the negative control group. Decocta of Urena lobata leave was given to P1 at 125 mg / l), P2 250 mg / l, and P3 500mg / l. SOD levels were measured using WST-1 assay kit and swimming speed were observed with tracker software. Data for SOD was analyzed using Kruskall-Wallis while swimming speed using one way ANOVA with a significance level of p <0.05Results: Decocta of Urena lobata leaves at a dose of 125mg / l, 250mg / l and 500mg / l inhibits decrease of SOD levels about 30% in P1, 2-fold in P2 and 50% in P3 compared to positive control (p < 0,05), and also of swimming speed about 50% in P1, 60% in P2 and 80% in P3 compared to positive controls (p <0,05).Conclusion: Urena lobata leaves decocta was able to inhibit decrease of SOD levels and swimming speed of Danio rerio chronically exposed to malathion.Keywords: Urena lobata, malathion, SOD, motility